Physicochemical Characterization and Dissolution Study of Solid Dispersion Tablet of Azithromycin (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: To increase the solubility of azithromycin by formulating solid dispersion (SD) and then SD tablets (SDT) were prepared from the best formulation of SDs. Material and Methods: SDs were prepared using polyethylene glycol 6000 and Î²-cyclodextrin (Î²-CD) by solvent evaporation method. To investigate drug-excipient interaction and for selection of suitable excipient for formulation differential scanning calorimetry study was done, and each excipient was selected for formulation development only if it showed compatible results. Results and Discussion: Tablets were prepared by direct compression technique using hydroxypropylmethylcellulose (HPMC)-K 100 and guar gum in different concentrations. SDs were evaluated for drug content, in vitro dissolution profiles, and developed SDT were evaluated for various pharmaceutical characteristics, viz., hardness, friability, weight variation, thickness, drug content, and in vitro drug release. Conclusion: Study indicates that among various formulations SDT of azithromycin: Î²-CD (1:2) complexes prepared using HPMC and guar gum in 1:4 combination showed maximum drug release.